Structure coating structure, coating composition, and method for manufacturing same
By using a coating composition containing the (meth)acrylate monomer unit polymer, epoxy compound and aminosilane compound partial reaction products, the problem of insufficient bonding and adhesion of the primer layer during roof repair is solved, and the problem of insufficient bonding and adhesion of the primer layer during roof repair is achieved. The sheets are firmly adhered to the roof and prevented from leaking rain.
Patent Information
- Application Number
- CN202380053893.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-29
- Filing Date
- 2023-08-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Prior art When repairing or reinforcing roofs and other structures, it is difficult to obtain primer layers with excellent bonding and adhesion, especially when roofs have been severely deteriorated.
A coating composition is used that contains a polymer containing a monomer unit of (meth)acrylate in the backbone, and a partial reaction product containing a mixture of an epoxy compound and an aminosilane compound.
The primer layer obtained by the coating composition has excellent adhesion and can effectively adhere the sheet to the roof, thereby solving the problem of rain leakage after roof deterioration.
Smart Images

Figure CN119486874A_ABST
Abstract
Description
Technical Field
[0001] This specification discloses a coating composition for application to a structure or the like. Background Art
[0002] Artificial slate is generally used for residential roofs. When the slate roof is exposed to wind and rain for a long time, deterioration occurs in the roof. The deteriorated slate roof may leak rain. The slate roof is coated with a coating material to prevent the leaking rain. However, when the slate roof has been severely deteriorated, the leaking rain may not be prevented even by coating the roof with a coating material.
[0003] Japanese Patent Application Publication No. 2022-101896 discloses a method for repairing a roof using a sheet having a polymer cement layer and a resin layer. Pasting the sheet to the roof makes it possible to suppress roof leakage.
[0004] Reference List Patent Literature PTL 1: Japanese Patent Application Publication No. 2022-101896. Summary of the invention
[0005] Technical issues Before the sheet is pasted on the roof, a coating material may be applied to the roof. The coating film obtained by the coating material can act as a primer layer. The primer layer enables the sheet to be firmly adhered to the roof. In other words, the primer layer requires excellent bonding adhesion.
[0006] When repairing roofs other than slate roofs, a primer layer having excellent bonding adhesion is required. Even when repairing or reinforcing structures other than roofs, a primer layer having excellent bonding adhesion is required.
[0007] The applicant's intention is to provide a coating composition from which a coating film having excellent cohesive adhesion can be obtained.
[0008] Solution to the problem The coating composition disclosed in this specification contains (1) A polymer comprising an alkyl (meth)acrylate monomer unit in its main chain, and (2) A partial reaction product of a mixture containing an epoxy compound and an aminosilane compound.
[0009] Advantageous Effects of the Invention A coating film that facilitates adhesive adhesion can be obtained from the coating composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] [ Figure 1 ] Figure 1is a front view showing a cladding construction together with a roof according to one embodiment; [ Figure 2 ] Figure 2 is along Figure 1 An enlarged cross-sectional view of line II-II in FIG. [ Figure 3 ] Figure 3 It is shown that the Figure 1 An enlarged cross-sectional view of a portion of a sheet in a cladding configuration; [ Figure 4 ] Figure 4 It is shown that the Figure 3 An enlarged plan view of a portion of the reinforcement in the sheet. DETAILED DESCRIPTION
[0011] Hereinafter, preferred embodiments will be described in detail with appropriate reference to the accompanying drawings.
[0012] [Covering structure] Figure 1 The roof 2 and the covering structure 4 are shown as structures. Figure 2 As shown, the cladding structure 4 has a primer layer 6 and a sheet 8. The cladding structure 4 covers the roof 2.
[0013] [Primer layer] The primer layer 6 is formed by applying a coating composition to the roof 2 and drying the coating composition. The primer layer 6 exists between the roof 2 and the sheet 8. The primer layer 6 increases the degree of adhesion between the sheet 8 and the roof 2. The primer layer allows the sheet 8 to be firmly adhered to the roof 2. Figure 2 The arrow TP in shows the thickness of the primer layer 6. From the viewpoint of the bonding adhesion of the sheet 8 to the roof 2, the thickness TP is preferably 50 µm or more, more preferably 100 µm or more, and particularly preferably 150 µm or more. From the viewpoint of ease of construction, the thickness TP is preferably 500 µm or less, more preferably 400 µm or less, and particularly preferably 350 µm or less.
[0014] The coating composition for the primer layer 6 contains (1) A polymer comprising an alkyl (meth)acrylate monomer unit in the main chain, and (2) a partial reaction product of a mixture containing an epoxy compound and an aminosilane compound, The polymer (1) containing a (meth) alkyl ester monomer unit in the main chain is a so-called acrylic polymer. The primer layer 6 obtained from the coating composition can contribute to the initial bonding and long-term bonding of the sheet 8 to the roof 2. The initial bonding is the bonding immediately after the sheet 8 is attached to the roof 2. The long-term bonding is the bonding after a long period of time has passed after the sheet 8 is attached to the roof 2.
[0015] [Acrylic polymer] "(Meth) acrylic acid" in this specification means any one or both of acrylic acid and methacrylic acid. The polymer is obtained by polymerization of a monomer. The polymer comprises a plurality of units. Each unit is derived from a monomer. In this specification, the unit will be referred to as a "monomer unit". A polymer comprising a (meth) acrylic acid alkyl ester monomer unit in the main chain can contribute to the bonding adhesion of the coating composition. The polymer can particularly contribute to the bonding adhesion of the deteriorated artificial slate to the roof 2. The polymer may contain a (meth) acrylic acid alkyl ester monomer unit in the side chain as well as the main chain. The coating composition may contain two or more acrylic polymers.
[0016] As the (meth)acrylic acid alkyl ester monomer, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, myristyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, behenyl (meth)acrylate and biphenyl (meth)acrylate are exemplified. The acrylic polymer can be obtained by polymerization reaction of two or more monomers.
[0017] The acrylic polymer (1) may contain a monomer unit other than the (meth)acrylic acid alkyl ester monomer unit in the main chain. As the monomer from which the unit is derived, there are exemplified monomers containing a carboxyl group, such as acrylic acid and methacrylic acid; monomers containing an amide group, such as acrylamide, methacrylamide, N-hydroxymethyl acrylamide, and N-hydroxymethyl methacrylamide; monomers containing an epoxy group, such as glycidyl acrylate and glycidyl methacrylate; monomer units containing an amino group, such as diethylaminoethyl acrylate, diethylaminoethyl methacrylate, and aminoethyl vinyl ether; polyoxyethylene acrylate; and polyoxyethylene methacrylate. Copolymers of the monomers thereof and the (meth)acrylic acid alkyl ester monomer can contribute to the curability of the coating composition.
[0018] The acrylic polymer (1) may contain monomer units attributed to acrylonitrile, styrene, α-methylstyrene, alkyl vinyl ether, vinyl chloride, vinyl acetate, vinyl propionate, ethylene, etc. in the main chain.
[0019] The ratio of the alkyl (meth)acrylate monomer unit in the copolymer of the alkyl (meth)acrylate monomer and the different monomer is preferably 50% by mass or more, more preferably 70% by mass or more, and particularly preferably 80% by mass or more. The ratio may be 100% by mass.
[0020] The acrylic polymer (1) can be obtained by a vinyl polymerization method. Specifically, the acrylic polymer (1) can be obtained by a chain transfer agent method, an active radical polymerization method, etc. In the chain transfer agent method, polymerization is carried out with a chain transfer agent having a specific functional group, and a polymer having a functional group at the end can be obtained. In the active radical polymerization method, the polymerization growth end grows without causing a termination reaction, etc., thereby obtaining a polymer having a molecular weight almost as designed. In the active radical polymerization method, a termination reaction is unlikely to occur, and a polymer having a narrow molecular weight distribution (Mw / Mn is about 1.1 to 1.5) can be obtained. In the active radical polymerization method, a polymer having a low viscosity can be obtained. In the active radical polymerization method, a monomer having a specific functional group can be introduced into any position of the polymer. The polymerization method is described in Japanese Patent Application Publication No. 2003-313397. Any of a solution polymerization method and a bulk polymerization method can be adopted.
[0021] The polymerization reaction can be carried out in a mixed solution of a monomer, a radical initiator, a chain transfer agent, a solvent, etc. at a temperature of 50°C to 150°C. As the radical initiator, azobisisobutyronitrile and benzoyl peroxide are exemplified. As the chain transfer agent, mercaptans such as n-dodecyl mercaptan, tert-dodecyl mercaptan, and lauryl mercaptan are exemplified; and halogen-containing compounds are exemplified. As the solvent, ethers, hydrocarbons, and esters are exemplified.
[0022] The weight average molecular weight of the acrylic polymer (1) is preferably 500 or more and 100000 or less. The polymerization reaction of the acrylic polymer (1) is easy. The polymer is excellent in operability and compatibility with other compounds. From these viewpoints, the weight average molecular weight is more preferably 1000 or more and 50000 or less and particularly preferably 2000 or more and 30000 or less. The molecular weight is measured by gel permeation chromatography (in terms of polystyrene).
[0023] [Partial reaction products] As mentioned above, the coating composition comprises the partial reaction product (2) of the mixture containing epoxy compound and aminosilane compound. This partial reaction product (2) can play the effect of compatibilizer and bonding adhesion promoter. In addition, this partial reaction product (2) can also contribute to stable bond strength. The coating composition containing this partial reaction product (2) can contribute to the bonding adhesion of primer layer 6.
[0024] [Epoxides] As the epoxy compound, there are exemplified a glycidyl ether type compound obtained by a reaction between a polyphenol such as bisphenol A, bisphenol F, bisphenol S, hexahydrobisphenol A, tetramethylbisphenol A, pyrocatechol, resorcinol, cresol novolac, tetrabromobisphenol A, trihydroxybiphenyl, bisresorcinol, bisphenol hexafluoroacetone, tetramethylbisphenol F or dixylenol and epichlorohydrin; a polyglycidyl ether type compound obtained by a reaction between an aliphatic polyol such as glycerol, neopentyl glycol, ethylene glycol, propylene glycol, butanediol, hexylene glycol, polyethylene glycol or polypropylene glycol and epichlorohydrin; a glycidyl ether ester type compound obtained by a reaction between a hydroxycarboxylic acid such as p-oxybenzoic acid or β-oxynaphthoic acid and epichlorohydrin; Polyglycidyl ester type compounds derived from polycarboxylic acids such as phthalic acid, methylphthalic acid, isophthalic acid, terephthalic acid, tetrahydrophthalic acid, hexahydrophthalic acid, endomethylenetetrahydrophthalic acid, endomethylenehexahydrophthalic acid, trimellitic acid or polymerized fatty acids; glycidyl aminoglycidyl ether type compounds derived from aminophenol or aminoalkylphenol; glycidyl aminoglycidyl ester type compounds derived from aminobenzoic acid; and glycidylamine type compounds derived from aniline, toluidine, tribromoaniline, diphenyldimethylamine, diaminocyclohexane, bisaminomethylcyclohexane, 4,4'-diaminodiphenylmethane or 4,4'-diaminodiphenylsulfone. In addition, as epoxy compounds, epoxidized polyolefins, glycidyl hydantoin, glycidyl alkylhydantoin and triglycidyl cyanurate are exemplified. In addition, as the epoxy compound, monoepoxides such as butyl glycidyl ether, phenyl glycidyl ether, alkylphenyl glycidyl ether, benzoic acid glycidyl ester and styrene oxide are exemplified. The epoxy compound may be a polymer of a compound containing two or more epoxy groups in the molecule. The partial reaction product (2) may be derived from two or more epoxy compounds.
[0025] Aliphatic epoxy compounds are preferred. Examples of the epoxy compounds include the above-mentioned glycidyl ether type compounds obtained by the reaction between polyphenols and epichlorohydrin. The epoxy compounds have excellent reactivity at low temperatures. The epoxy compounds can contribute to the bonding strength and weather resistance of the primer layer 6. Aliphatic epoxy compounds contain at least one aliphatic ring other than an aromatic ring in one molecule and contain at least one epoxy group. From the perspective of easy procurement, epoxy compounds containing sorbitol, glycerol, diglycerol or polyglycerol as a parent skeleton are preferred.
[0026] [Aminosilane compounds] Preferred aminosilane compounds have at least one of an amino group and / or an imino group and at least one hydrolyzable silicon-containing group. Examples of the aminosilane compound include γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylethyldiethoxysilane, bistrimethoxysilylpropylamine, bistriethoxysilylpropylamine, bismethoxydimethoxysilylpropylamine, bisethoxydiethoxysilylpropylamine, N-β (aminoethyl) γ-aminopropyltrimethoxysilane, N-β (aminoethyl) γ-aminopropylmethyldimethoxysilane, and γ-aminopropylethyldiethoxysilane. alkyl, N-β (aminoethyl) γ-aminopropyl triethoxysilane, N-β (aminoethyl) γ-aminopropyl ethyl diethoxysilane, 3,3-dimethyl-4-aminobutyl trimethoxysilane, 3,3-dimethyl-4-aminobutyl methyl dimethoxysilane, (N-cyclohexylaminomethyl) methyl diethoxysilane, (N-cyclohexylaminomethyl) triethoxysilane, (N-phenylaminomethyl) methyl dimethoxysilane and (N-phenylaminomethyl) trimethoxysilane.
[0027] As other preferred aminosilane compounds, a compound having a structure represented by the following formula (I) and a compound having a structure represented by the following formula (II) are exemplified.
[0028] [C1] .
[0029] [C2] .
[0030] The partial reaction product (2) may be derived from two or more aminosilane compounds.
[0031] [mixture] For the partial reaction product (2), the ratio (Y / X) of the number of amino and / or imino groups (Y) in the aminosilane compound to the number of epoxy groups (X) in the epoxy compound in the mixture is preferably 0.2 or more and 1.5 or less. The ratio (Y / X) is more preferably 0.4 or more and particularly preferably 0.5 or more. The (Y / X) is more preferably 1.3 or less and particularly preferably 1.2 or less.
[0032] The mixture for the partial reaction product (2) may contain compounds other than epoxy compounds and aminosilane compounds. As preferred compounds, epoxy compounds containing alkoxysilanes are exemplified. The epoxy compounds containing alkoxysilanes have excellent compatibility with the reaction products of epoxy compounds and aminosilane compounds. The epoxy compounds containing alkoxysilanes can act as an accelerator for wet curability in the coating composition. The epoxy compounds containing alkoxysilanes can contribute to the curability of the coating composition. The partial reaction product (2) containing epoxy compounds containing alkoxysilanes is suitable for long-term storage. In addition, the primer layer 6 obtained from the coating composition can suppress the scattering of dust from the roof 2 when the sheet 8 has been peeled off from the roof 2. In other words, the primer layer 6 has excellent sealing properties.
[0033] As the alkoxysilane-containing epoxy compound, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane are exemplified.
[0034] The ratio of the amount of the alkoxysilane-containing epoxy compound in the total amount of the epoxy compound, the aminosilane compound and the alkoxysilane-containing epoxy compound in the mixture is preferably 10% by mass or more and 40% by mass or less in terms of solid content. The ratio is more preferably 15% by mass or more and particularly preferably 20% by mass or more. The ratio is more preferably 35% by mass or less and particularly preferably 30% by mass or less.
[0035] A mixture containing an epoxy compound and an aminosilane compound is subjected to a known reaction. The reaction process between the epoxy compound and the aminosilane compound produces a reaction product, which may cause gelation of the mixture. A partial reaction product (2) can be obtained by terminating the reaction at a stage where the gelation does not occur. As a method for terminating the reaction, diluting the mixed solution with a solvent (such as ethanol) is exemplified.
[0036] The gel fraction in the partial reaction product (2) is preferably 15% or more and 85% or less. A coating composition having excellent sealing properties can be obtained from the partial reaction product (2) having a gel fraction of 15% or more. From this viewpoint, the gel fraction is more preferably 30% or more and particularly preferably 35% or more. A coating composition having an appropriate viscosity can be obtained from the partial reaction product (2) having a gel fraction of 85% or less. From this viewpoint, the gel fraction is more preferably 70% or less and particularly preferably 60% or less.
[0037] [Coating composition] As mentioned above, the coating composition contains (1) A polymer comprising an alkyl (meth)acrylate monomer unit in the main chain, and (2) a partial reaction product of a mixture containing an epoxy compound and an aminosilane compound, The amount of the partial reaction product (2) is preferably 1 part by mass or more and 150 parts by mass or less relative to 100 parts by mass of the acrylic polymer (1). From the coating composition, a primer layer 6 that facilitates the attachment of the sheet 8 can be obtained. From this viewpoint, the amount of the partial reaction product (2) is more preferably 30 parts by mass or more and particularly preferably 50 parts by mass or more.
[0038] The coating composition may contain an organic solvent. The amount of the organic solvent is preferably 250 parts by mass or more and 400 parts by mass or less relative to 100 parts by mass of the acrylic polymer (1).
[0039] The coating composition may contain a silane coupling agent. The silane coupling agent can contribute to the bonding adhesion of the primer layer 6. The silane coupling agent comprises at least one functional group that reacts with an organic group in the molecule of the partial reaction product (2). The silane coupling agent further comprises at least one hydrolyzable silicon group. As the functional group, methacrylic acid group, acrylic acid group, isocyanate group, isocyanurate group, vinyl group, carbamate group and epoxy group are exemplified. The silane coupling agent may comprise two or more functional groups. From the perspective of the curability of the coating composition and the bonding adhesion of the primer layer 6, methacrylic acid group, acrylic acid group and epoxy group are preferred. From the perspective of operability, the preferred hydrolyzable silicon group is an alkoxysilyl group. From the perspective of reactivity, particularly preferred hydrolyzable silicon groups are methoxysilyl and ethoxysilyl.
[0040] As preferred silane coupling agents, alkoxysilanes having a methacrylic group or an acrylic group, such as γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-acryloxypropyltrimethoxysilane, γ-acryloxypropyltriethoxysilane, methacryloxymethyltrimethoxysilane, methacryloxymethyltriethoxysilane, acryloxymethyltrimethoxysilane and acryloxymethyltriethoxysilane; and epoxy-containing silane compounds, such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and γ-glycidoxypropylmethyldiethoxysilane.
[0041] From the viewpoint of adhesiveness, the amount of the silane coupling agent is preferably 1 part by mass or more relative to 100 parts by mass of the acrylic polymer (1). From the viewpoint of physical properties of the primer layer 6, the amount is preferably 100 parts by mass or less and particularly preferably 50 parts by mass or less.
[0042] The coating composition may contain a reinforcing agent. The reinforcing agent can contribute to the strength of the primer layer 6. Examples of reinforcing agents include organic fine particles and inorganic fine particles. From the perspective of heat resistance, inorganic fine particles are preferred. As materials for inorganic particles, silicon dioxide, titanium dioxide, aluminum oxide, zirconium oxide, cerium dioxide and calcium carbonate are exemplified.
[0043] The amount of the reinforcing agent is preferably 1 part by mass or more relative to 100 parts by mass of the acrylic polymer (1) from the viewpoint of the strength of the primer layer 6. From the viewpoint of the adhesive adhesion of the primer layer 6, the amount is preferably 100 parts by mass or less and particularly preferably 60 parts by mass or less.
[0044] The particle size of the reinforcing agent is preferably 1.0 μm or less and particularly preferably 0.5 μm or less from the viewpoint of transparency of the primer layer 6. From the viewpoint of transparency, a reinforcing agent having a refractive index substantially equal to that of the matrix is preferred.
[0045] The coating composition may further contain different polymers. The coating composition may also contain different additives. As additives, reaction retarders, anti-aging agents, antioxidants, pigments, dyes, plasticizers, thixotropic agents, UV absorbers, flame retardants, solvents, surfactants, leveling agents, dispersants, dehydrating agents, tackifiers, antistatic agents and fillers are exemplified.
[0046] The coating composition is excellent in curability, pot life and workability. A primer layer 6 having excellent initial bonding adhesion, long-term bonding adhesion, sealing properties and insect repellency can be obtained from the coating composition.
[0047] [Method for producing coating composition] The coating composition can be obtained by stirring a mixed solution of a solution or dispersion containing the acrylic polymer (1) and a solution or dispersion containing the partial reaction product (2). For stirring, a stirring device such as a ball mill can be used. The stirring disperses the solid content in the solvent. A typical solvent is ethanol. An additive can be added to the mixed solution together with the solvent (such as ethylbenzene).
[0048] [Sheet] like Figure 3 As shown, the sheet 8 has a functional layer 10, an intermediate layer 12, an adhesive layer 14 and a reinforcement 16. The reinforcement 16 is embedded in the intermediate layer 12.
[0049] [Functional layer] As from Figure 3 As is apparent from the figure, in the embodiment of the present invention, the functional layer 10 is located at the top of the sheet 8. In other words, when the sheet 8 has been attached to the structure, the position of the functional layer 10 is farthest from the structure in the thickness direction. The functional layer 10 contributes to the desired functions of the sheet 8. As these functions, weather resistance, wear resistance, chemical resistance, water impermeability, moisture impermeability and moisture permeability are exemplified. Typical weather resistance is heat resistance and light resistance. The functional layer 10 can contribute to one or two or more functions.
[0050] The preferred material of the functional layer 10 is a polymer composition. The functional layer 10 is generally flexible. The sheet 8 having the functional layer 10 can conform to the unevenness on the roof 2. The polymer composition contains a base polymer. Synthetic resins, synthetic rubbers and natural rubbers can be included in the composition as base polymers. As preferred base polymers, acrylic resins, acrylic urethane resins, acrylic silicone resins, fluororesins, flexible epoxy resins and polybutadiene are exemplified. When the base polymer is a synthetic resin, the functional layer 10 is also referred to as a "resin layer".
[0051] From the perspective of light resistance, acrylic silicone resin is a resin that is particularly suitable as a base polymer for the functional layer 10. Acrylic silicone resin has a siloxane bond. Acrylic silicone resin is also excellent in heat resistance and cold resistance. Specific examples of compositions containing acrylic silicone resins include product names "COOL LIFE SP Black (CB1) P5-0" manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd., product names "Belle Earth Elastic Black" manufactured by Fujikura Kasei Co., Ltd., product names "ARONBULLCOAT T-1000" manufactured by Toagosei Co., Ltd., and product names "ACRYSET EMN-325E" and "UWR EF-008" manufactured by NIPPON SHOKUBAI CO., LTD.
[0052] As required, the polymer composition of the functional layer 10 may contain additives such as pigments, fillers, reinforcing materials and antifouling agents. The functional layer 10 containing pigments has excellent designability. The polymer composition may contain organic pigments and inorganic pigments. As fillers, metal oxide particles such as silicon dioxide, aluminum oxide and titanium dioxide are exemplified. As reinforcing materials, cellulose nanofibers are exemplified. The content of each additive is adjusted according to the function.
[0053] Figure 3 The arrow T1 in represents the thickness of the functional layer 10. From the viewpoint of functionality, the thickness T1 is preferably 10 μm or more, more preferably 30 μm or more and particularly preferably 50 μm or more. From the viewpoint of compliance, productivity and lightweight of the sheet 8, the thickness T1 is preferably 500 μm or less, more preferably 300 μm or less and particularly preferably 150 μm or less. The distribution of the thickness T1 is preferably within the range of ± 50 μm. The sheet 8 may include two or more functional layers 10.
[0054] [Middle layer] The intermediate layer 12 contributes to the rigidity of the sheet 8, etc. The preferred material of the intermediate layer 12 is a composite material of a polymer and a filler. As the polymer of the composite material, acrylic resin, acrylic silicone resin, fluororesin, silicone resin, epoxy resin, ethylene-vinyl acetate copolymer and styrene-butadiene copolymer are exemplified. As the filler of the composite material, cement, silica, alumina, titanium oxide, calcium carbonate and carbon black are exemplified. The preferred composite material is polymer cement. The polymer cement includes a polymer and cement. The cement is in a state of being dispersed in a matrix of the polymer. The polymer is typically an acrylic resin. As cement, Portland cement, alumina cement and a mixture thereof are exemplified. Portland cement is preferred. The intermediate layer 12 made of polymer cement is also referred to as a "polymer cement cured layer".
[0055] When the intermediate layer 12 contains a polymer and cement, the mass ratio of the polymer relative to the solid content of the intermediate layer 12 is preferably 10% or more and 40% or less. When the ratio is 10% or more, the intermediate layer 12 has excellent adhesion to other layers (functional layer 10 or adhesive layer 148). From this viewpoint, the ratio is more preferably 15% or more and particularly preferably 20% or more. When the ratio is 40% or less, the intermediate layer 12 can contain a sufficient amount of cement. From this viewpoint, the ratio is more preferably 35% or less and particularly preferably 30% or less.
[0056] When the intermediate layer 12 contains a polymer and cement, the mass ratio of cement relative to the solid content of the intermediate layer 12 is preferably 20% or more and 70% or less. When the ratio is 20% or more, high tensile strength and low elongation can be achieved in the sheet 8 including the intermediate layer 12. The sheet 8 has excellent handleability. From this viewpoint, the ratio is more preferably 30% or more and particularly preferably 35% or more. When the ratio is 70% or less, the intermediate layer 12 can contain a sufficient amount of polymer. From this viewpoint, the ratio is more preferably 60% or less and particularly preferably 55% or less.
[0057] The intermediate layer 12 can be formed from a mixed solution obtained from a composition containing a polymer and a composition containing cement. A preferred composition containing a polymer is an acrylic emulsion. The acrylic emulsion can be obtained by emulsion polymerization of a monomer. The emulsion polymerization can be carried out using an emulsifier. The polymerization can be carried out in water containing a surfactant. The monomer is typically an acrylate or a methacrylate. The content of the monomer component of the acrylic emulsion is preferably 20% to 100% by mass.
[0058] Specific examples of the composition containing a polymer include a product name "Spring Coat Brush mixed solution" manufactured by KIKUSUI Chemical Industries Co., Ltd. and a product name "ARONBULLCOAT A450 base" manufactured by Toagosei Co., Ltd. Specific examples of the composition containing cement include a product name "Spring Coat Brush powder" manufactured by KIKUSUI Chemical Industries Co., Ltd. and a product name "ARONBULLCOAT A450 Setter" manufactured by Toagosei Co., Ltd.
[0059] The intermediate layer 12 containing polymer and cement has excellent water vapor permeability. Therefore, when a structure is covered with the sheet 8 including the intermediate layer 12, the metal in the structure is not easily corroded. The water vapor permeability of the intermediate layer 12 is preferably 20 g / m 2 · days or more and 60 g / m 2 · days or less. The water vapor transmission rate is measured in accordance with the provisions of "JIS Z0208".
[0060] Figure 3 The arrow T2 in 1 represents the thickness of the intermediate layer 12. In the present embodiment, as described above, the reinforcement 16 is embedded in the intermediate layer 12. Therefore, the thickness T2 including the reinforcement 16 is measured. From the viewpoint of the operability of the sheet 8, the thickness T2 is preferably 100 μm or more, more preferably 300 μm or more and particularly preferably 500 μm or more. From the viewpoint of the compliance, productivity and light weight of the sheet 8, the thickness T2 is preferably 1500 μm or less, more preferably 1000 μm or less and particularly preferably 700 μm or less. The distribution of the thickness T2 is preferably within the range of ± 100 μm.
[0061] The material of the intermediate layer 12 may be a resin composition or a rubber composition. The sheet 8 may include two or more intermediate layers 12. The sheet 8 may include two intermediate layers 12 of different materials. The sheet 8 may have a layer configuration that does not include the intermediate layer 12.
[0062] From the viewpoint of the adhesion between the intermediate layer 12 and the functional layer 10 , the base polymer of the intermediate layer 12 is preferably the same type as the base polymer of the functional layer 10 .
[0063] [Adhesive layer] The adhesive layer 14 (or bonding adhesive layer) is in contact with the primer layer 6. The sheet 8 can be attached to the structure by the adhesive force of the adhesive layer 14.
[0064] The preferred material of the adhesive layer 14 is an adhesive composition containing a polymer as a base material. As polymers suitable for the adhesive composition, acrylic resins, silicones, polyurethanes, polyesters, natural rubbers and synthetic rubbers are exemplified. For the base material, acrylic resins are particularly preferred polymers. Specific examples of the adhesive composition include product names "ORIBAIN BPS 6574", "ORIBAIN BPS6554" and "ORIBAIN BPS 5565K" manufactured by TOYOCHEM CO., Ltd. From the perspective of the adhesion of the adhesive layer 14 to the intermediate layer 12, the base polymer of the adhesive layer 14 is preferably the same type as the base polymer of the intermediate layer 12. From the perspective of the adhesion of the adhesive layer 14 to the primer layer 6, the base polymer of the adhesive layer 14 is preferably the same type as the base polymer of the primer layer 6.
[0065] The adhesive composition may contain a curing agent. As preferred curing agents, curing agents based on isocyanates, curing agents based on amines, curing agents based on epoxy resins, and curing agents based on metal chelates are exemplified. When the base material is an acrylic resin, a preferred curing agent is an isocyanate curing agent. The ratio of the isocyanate curing agent to 100 parts by mass of the acrylic resin is preferably 1.0 parts by mass or more, more preferably 2.0 parts by mass or more, and particularly preferably 2.5 parts by mass or more. The ratio is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and particularly preferably 7 parts by mass or less.
[0066] The adhesive composition may contain a tackifier. As tackifiers, rosin-based tackifiers, terpene-based tackifiers, petroleum resin-based tackifiers, and phenolic resin-based tackifiers are exemplified. The ratio of tackifier to 100 parts by mass of base polymer is preferably 0.5 parts by mass or greater, more preferably 1.0 parts by mass or greater, and particularly preferably 1.5 parts by mass or greater. The ratio is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, and particularly preferably 7 parts by mass or less. Specific examples of tackifiers include product names "ESTER GUM H", "ESTER GUM AA-V", and "ESTER GUM 105" manufactured by ARAKAWA CHEMICAL INDUSTRIES, LTD.
[0067] Figure 3The arrow T3 in FIG. 1 represents the thickness of the adhesive layer 14. From the viewpoint of adhesion, the thickness T3 is preferably 20 μm or more, more preferably 40 μm or more, and particularly preferably 50 μm or more. From the viewpoint of productivity, lightness, and operability of the sheet 8, the thickness T3 is preferably 500 μm or less, more preferably 200 μm or less, and particularly preferably 150 μm or less. The amount of the adhesive layer 14 is preferably 20 g / m 2 or larger and 250 g / m 2 The sheet 8 may include two or more adhesive layers 14 .
[0068] [Reinforcement] The reinforcement 16 can give the sheet 8 an appropriate Young's modulus. The reinforcement 16 can contribute to the large tensile strength of the sheet 8. In addition, the reinforcement 16 can contribute to the small elongation of the sheet 8. The sheet 8 including the reinforcement 16 has excellent operability. As described above, the reinforcement 16 is embedded in the intermediate layer 12. The reinforcement 16 can also be embedded in the functional layer 10. The reinforcement 16 can also be embedded in the adhesive layer 14. The reinforcement 16 can be located between the functional layer 10 and the intermediate layer 12. The reinforcement 16 can be located between the intermediate layer 12 and the adhesive layer 14. In this specification, the reinforcement 16 means an object that can give the sheet 8 a large tensile strength compared to a hypothetical sheet having the same layer structure as the sheet 8 but not including the reinforcement 16.
[0069] The tensile strength of the reinforcement 16 is preferably 5.0 MPa or more. When the tensile strength of the reinforcement 16 is 5.0 MPa or more, the sheet 8 is less likely to break even when tension is applied thereto. The sheet 8 has excellent handleability. From this point of view, the tensile strength is more preferably 5.5 MPa or more and particularly preferably 6.0 MPa or more. From the point of view of the compliance of the sheet 8, the tensile strength of the reinforcement 16 is preferably 15.0 MPa or less, more preferably 10.0 MPa or less and particularly preferably 7.0 MPa or less.
[0070] The elongation at break of the reinforcement 16 is preferably 15.0% or less. When the elongation of the reinforcement 16 is 15.0% or less, the sheet 8 is less likely to be deformed even when tension is applied thereto. The sheet 8 has excellent handleability. From this point of view, the elongation of the reinforcement 16 is more preferably 13.0% or less and particularly preferably 11.0% or less. From the point of view of the compliance of the sheet 8, the elongation of the reinforcement 16 is preferably 5.0% or more, more preferably 7.0% or more and particularly preferably 8.5% or more.
[0071] The tensile strength and elongation were measured according to the test method for nonwovens specified in "JIS L1913: 2010". Test pieces for measurement were cut out from the reinforcement 16 or its original fabric. Five test pieces in which the length direction coincided with the length direction of the reinforcement 16 or its original fabric and five test pieces in which the length direction coincided with the width direction of the reinforcement 16 or its original fabric were used in the measurement. The tensile strength and elongation were calculated by averaging ten measured values.
[0072] In a plan view, the ratio of the area of the outline of the reinforcement 16 to the area of the sheet 8 is preferably 60% or more. When the ratio is 60% or more, the reinforcement 16 can contribute to the operability of the sheet 8. From this point of view, the ratio is more preferably 70% or more and particularly preferably 75% or more. The ratio may be 100%. From the point of view of compliance with the step difference of the sheet 8, the ratio is preferably 95% or less.
[0073] [Fabric] Figure 4 A reinforcement 16 is shown. In the reinforcement 16, a plurality of warp threads 18a and a plurality of weft threads 18b are woven. In other words, the reinforcement 16 is a woven fabric (cloth). In an embodiment of the present invention, the woven fabric has a plain weave structure. A woven fabric is a kind of fabric. The reinforcement 16 (which is a fabric) can be impregnated with the composition of the intermediate layer 12. The impregnation can contribute to the large tensile strength of the sheet 8. The impregnation can also contribute to the small elongation of the sheet 8. The reinforcement 16 can be a fabric other than a woven fabric. As fabrics other than woven fabrics, knitted fabrics (knitted fabrics) and cross-welded meshes are exemplified.
[0074] As the material of the reinforcement 16, synthetic resin compositions and metals are exemplified. As preferred base material resins for the synthetic resin composition, polyethylene terephthalate, polyethylene naphthalate, aramid, vinylon, polypropylene, polystyrene and polyvinylidene fluoride are exemplified. As preferred metals, aluminum alloys, carbon steel and alloy steel are exemplified. A sufficiently high tensile strength of the sheet 8 can be achieved by adopting the warp 18a and weft 18b having high tensile strength. A sufficiently low elongation of the sheet 8 can be achieved by adopting the warp 18a and weft 18b having small elongation.
[0075] As from Figure 4 As is apparent from the figure, the reinforcement 16 comprises a large number of meshes 20. In the present embodiment, each mesh 20 has a substantially square planar shape. The intermediate layer 12 penetrates the meshes 20. This penetration can contribute to the large tensile strength of the sheet 8. This penetration can also contribute to the small elongation of the sheet 8.
[0076] Figure 4The arrow P1 in represents the spacing of the yarn 18. The spacing P1 is preferably 1.2 mm or more and 50 mm or less. When the spacing P1 in the reinforcement 16 is 1.2 mm or more, the reinforcement 16 is sufficiently impregnated with the composition of the intermediate layer 12. The reinforcement 16 can contribute to the large tensile strength and small elongation of the sheet 8. From this point of view, the spacing P1 is more preferably 1.5 mm or more and particularly preferably 1.7 mm or more. When the spacing P1 in the reinforcement 16 is 50 mm or less, the reinforcement 16 can contribute to the large tensile strength and small elongation of the sheet 8. From this point of view, the spacing P1 is more preferably 40 mm or less and particularly preferably 35 mm or less.
[0077] Figure 4 The arrow D1 in shows the thickness of the yarn 18. The yarn 18 having a large thickness D1 enables high tensile strength and small elongation of the sheet 8. From this point of view, the thickness D1 is preferably 0.05 mm or more, more preferably 0.10 mm or more, and particularly preferably 0.15 mm or more. The thickness is preferably 1.0 mm or less.
[0078] The sheet 8 may include a non-woven reinforcement 16. As the non-woven reinforcement 16, non-woven fabrics, long fibers, resin films, and metal foils are exemplified. The reinforcement 16 may also be a large number of short fibers dispersed in the composition. The sheet 8 may have a layer structure that does not include the reinforcement 16.
[0079] [Different layers] The sheet 8 may include a different layer located on the functional layer 10. A typical different layer is a transparent paint layer. The sheet 8 may also include a layer located between the functional layer 10 and the intermediate layer 12. The sheet 8 may also include a layer located between the intermediate layer 12 and the adhesive layer 14.
[0080] [Total thickness] Figure 3 The arrow TS in represents the total thickness of the sheet 8. The total thickness TS is preferably 200 μm or more, more preferably 400 μm or more and particularly preferably 500 μm or more. The total thickness TS is preferably 5.0 mm or less, more preferably 3.0 mm or less and particularly preferably 1.0 mm or less. The distribution of the total thickness TS is preferably within the range of ± 100 μm.
[0081] [Characteristics of Sheet Material] The water vapor transmission rate of the sheet 8 is preferably 10 g / m 2· day or more. After the sheet 8 is pasted on the roof 2, moisture contained in the roof 2 or moisture existing between the roof 2 and the sheet 8 can be discharged through the sheet 8. The sheet 8 can suppress corrosion of metal in the roof 2. The sheet 8 is also suitable for structures containing moisture (for example, structures containing concrete that is not completely dried). The sheet 8 is also suitable for construction in rainy weather. From these viewpoints, the water vapor transmission rate is more preferably 20 g / m 2 day or more and particularly preferably 25 g / m 2 · days or more. The water vapor transmission rate is preferably 50 g / m 2 · days or less. The water vapor transmission rate is measured in accordance with the provisions of "JIS Z0208".
[0082] The peel strength of the sheet 8 in a 180° peel test is preferably 1.5 N / 25 mm or more. Even in strong winds, the sheet 8 is unlikely to peel off from the roof 2. From this viewpoint, the peel strength is more preferably 5.0 N / 25 mm or more and particularly preferably 8.0 N / 25 mm or more.
[0083] The peel strength is measured by a 180° peel test in accordance with the provisions of "JIS Z 0237: 2022". The details of the test piece are as follows: Production of test pieces: In accordance with Section 10.1 of JIS Z 0237: 2022 PET film: 25 mm x 200 mm, "T601E" manufactured by Mitsubishi Chemical Corporation, thickness: 50 µm) Double-sided tape: 25 mm x 100 mm, "No. 5015" manufactured by Nitto Denko Technical Corporation Sheet: Cut into 25 mm x 100 mm Substrate: Steel plate (SUS30) specified in Section "10.2.2" of "JIS Z 0237: 2022", surface finish: BA (BASUS sheet), 75 mm x 150 mm.
[0084] The test pieces for measuring peel strength were produced by the following procedure: (1) Clean the surface of the BASUS board with MEK applied BEMCOT (M-3II manufactured by Asahi Kasei Corporation), (2) Use a tape pressing roller (mass: 2 kg) to stick one adhesive surface of the double-sided tape to the front surface of the sheet. (3) Use a tape pressing roller (mass: 2 kg) to stick the PET film to the other adhesive surface of the double-sided tape so that the short edges are aligned. (4) Use a pressure roller (mass: 2 kg) to stick the adhesive layer of the sheet to the BASUS board. The test pieces obtained through this procedure are stored in an environment of normal temperature and normal humidity (23°C ± 2°C, 50 ± 10%RH) for 24 hours.
[0085] The test was conducted in accordance with Section "11.5" of "JIS Z 0237: 2022". The measurement conditions are as described below: Load cell: 1 kN Temperature: 23°C ± 2°C Relative humidity: 50 ± 5%RH Speed: 300 mm / min Stripping length: 100 mm The measured values obtained until the length after the start of measurement reaches 30 mm are ignored. The measured values obtained when the 30 mm sheet is peeled off are then averaged. As an apparatus suitable for the test, a product name "AUTOGRAPH AGX-V 10 kN" manufactured by Shimadzu Corporation is exemplified.
[0086] [Method for producing sheet] Hereinafter, an example of a method for manufacturing the sheet 8 will be described. In the manufacturing method, a first coating material is obtained by mixing a polymer composition of the functional layer 10 with a solvent. A first coating film is obtained by applying the first coating material to a base film. The solvent is volatilized from the first coating material by heating the first coating film. The base polymer is cured by the heating, and the functional layer 10 is obtained. The functional layer 10 having a rough pattern can be obtained by applying the first coating material to a base film having a rough pattern on the surface. The rough pattern of the functional layer 10 has an inverted shape of the rough pattern shape of the base film.
[0087] Next, a second coating material is obtained by mixing the composite material of the intermediate layer 12 with a solvent. A second coating film is obtained by applying the second coating material to the functional layer 10. A reinforcement 16 is pressed onto the second coating film. The solvent is volatilized from the second coating material by heating the second coating film. The polymer is cured by the heating, and an intermediate layer 12 including the reinforcement 16 is obtained.
[0088] Next, a third coating material is obtained by mixing the adhesive composition of the adhesive layer 14 with a solvent. A third coating film is obtained by applying the third coating material to a release film. The solvent is volatilized from the third coating material by heating the third coating film, and the adhesive layer 14 is obtained.
[0089] The adhesive layer 14 is superposed on the intermediate layer 12. Furthermore, the base film is peeled off from the functional layer 10, and the release film is peeled off from the adhesive layer 14, thereby obtaining the sheet 8 for a structure. The base film or the release film may remain on the sheet 8 for a structure.
[0090] [Roof repair or reinforcement] When repairing the roof 2 with the above-mentioned covering structure 4, first, the deposits are removed from the surface of the roof 2, and then the coating composition is applied to the surface. The coating composition is dried, thereby obtaining the primer layer 6. Next, the sheet 8 is attached to the primer layer 6 by the adhesive force of the adhesive layer 14 of the sheet 8. After these steps, the covering structure 4 is completed. The roof 2 that does not need to be repaired can be reinforced by forming the covering structure 4 on the roof 2.
[0091] The sheet 8 has excellent conformability and can therefore be applied to the roof 2 having a step difference as described above. By pasting a plurality of sheets 8 together, the surface of the roof 2 is covered with the sheet 8 over a large area. The sheet 8 has the adhesive layer 14, and therefore it is not necessary to apply an adhesive (or bonding adhesive) to the roof 2. Since the adhesive layer 14 has excellent adhesion, even when the material of the surface of the roof 2 is a composite material, the surface of the roof 2 can be covered with the sheet 8 over a large area. For example, even when the roof 2 includes both metal and artificial slate on the surface, the surface of the roof 2 can be covered with the sheet 8 over a large area.
[0092] The entire surface of the roof 2 may be covered with the sheet 8. In this specification, the surface of the roof 2 means the surface visible when the roof 2 is viewed from above in the vertical direction. Repair in which the entire surface of the roof 2 is covered with a single type of sheet 8 is not found in conventional methods.
[0093] The sheet 8 is lighter than a steel plate, a copper plate, a galvanized iron plate, etc. Therefore, even when the surface of the roof 2 is covered with the sheet 8 over a large area, the adverse effect on the earthquake resistance of the building is small. From the viewpoint of earthquake resistance, the density of the sheet 8 is preferably 4.0 g / cm 3 or lower, more preferably 3.0 g / cm 3 or less and particularly preferably 2.5 g / cm 3 or lower. This density is much lower than that of the aluminum-zinc alloy steel sheet (product name "GALVALUME steel sheet") commonly used for repairing roofs 2.
[0094] [Adhesion workload of cladding structure] The adhesion workload W2 between the primer layer 6 and the adhesive layer 14 is smaller than the adhesion workload W1 between the structure such as the roof 2 and the primer layer 6. In the coating structure 4, when the sheet 8 is pasted on the primer layer 6 and then peeled off from the roof 2, the peeling occurs at the interface between the primer layer 6 and the adhesive layer 14. In other words, when the sheet 8 is peeled off, the peeling at the interface between the primer layer 6 and the adhesive layer 14 is suppressed. In the coating structure 4, when the sheet 8 is peeled off, the damage of the roof 2 is suppressed. In addition, in the coating structure 4, when the sheet 8 is peeled off, the scattering of dust from the roof 2 is suppressed. From these viewpoints, the ratio (W1 / W2) of the adhesion workload W1 to the adhesion workload W2 is preferably 1.20 or more, more preferably 1.23 or more and particularly preferably 1.25 or more. By obtaining the primer layer 6 from the above-mentioned coating composition, an appropriate ratio (W1 / W2) can be achieved.
[0095] The adhesion workload is related to the surface free energy. The adhesion workload W between the first solid and the second solid is calculated by the following formula: W = 2(γ SV1 d γ SV2 d ) 1 / 2 + 2(γ SV1 h γ SV2 h ) 1 / 2 γ SV1 d : The dispersion component of the surface free energy of the first solid γ SV2 d : The dispersion component of the surface free energy of the second solid γ SV1 h : The hydrogen bonding component of the surface free energy of the first solid γ SV2 h : The hydrogen bonding component of the surface free energy of the second solid.
[0096] In this specification, a drop of water and a drop of diiodomethane are used to measure the surface free energy. Surface free energy of water γ L1V1 is 72.8 mJ / m 2 The surface free energy γ LV1 It is calculated by the following formula: γ LV1 = γ LV1 d + γLV1 h γ LV1 d : Dispersive component of surface free energy γ LV1 h : Hydrogen bond component of surface free energy Surface free energy of diiodomethane γ LV2 is 50.8 mJ / m 2 The surface free energy γ LV2 It is calculated by the following formula: γ LV2 = γ LV2 d + γ LV2 h γ LV2 d : Dispersive component of surface free energy γ LV2 h : The hydrogen bond component of the surface free energy.
[0097] When the contact angle of water with the solid is indicated by θ1, and the contact angle of diiodomethane with the solid is indicated by θ2, the following formula is established: (γ SV d γ LV1 d ) 1 / 2 + (γ SV h γ LV1 h ) 1 / 2 = (γ L1 (1 + cosθ1)) / 2 (γ SV d γ LV2 d ) 1 / 2 + (γ SV h γ LV2 h ) 1 / 2 = (γ L2 (1 + cosθ2)) / 2 Solid Gamma SV d and γ SV hIt can be calculated by specifying the contact angles θ1 and θ2 with the solid in the formula. A sample for measuring the contact angle was obtained by applying the coating composition to a 188 µm thick PET film (trade name "COSMOSHINE A4300" manufactured by Toyobo Co., Ltd.). For application, an applicator was used. The application amount was 400 g / m 2 The coating composition was maintained at a temperature of 100° C. for five minutes. As a result, the coating composition was dried, and a sample was obtained.
[0098] In this specification, the contact angle (θ1 or θ2) is measured under an environment of 23°C. A 2 μL droplet (of water or diiodomethane) is added to a solid. The angle formed by these solids and liquids is measured. As an apparatus suitable for measurement, a portable contact angle meter "PCA-11" manufactured by Kyowa Interface Science Co., Ltd. is exemplified.
[0099] [Peel strength of coating structure] The 180° peeling force between the adhesive layer 14 and the primer layer 6 is preferably 1.5 N / 25 mm or more. The sheet 8 including the adhesive layer 14 having a peeling strength of 1.5 N / 25 mm or more can be firmly bonded to the roof 2. From this point of view, the peeling force is more preferably 7 N / 25 mm or more and particularly preferably 11 N / 25 mm or more. The peeling force is measured in accordance with the provisions of the above-mentioned "JIS Z 0237 (2022)". Instead of the BASUS board, a substrate consisting of a BASUS board and a primer layer 6 can be used.
[0100] [Other uses of cladding structures] These primer layers 6 and sheets 8 can help repair or reinforce structures other than the roof 2. Examples of structures other than the roof 2 include residential walls, pillars, eaves, fences, gates, doors, railings, copings, etc. These primer layers 6 and sheets 8 can also be used in commercial buildings, factories, warehouses, bridges, sewage facilities, railway facilities, utility poles, tunnels, etc.
[0101] [Repair and Reinforcement] After a structure (roof 2, etc.) is repaired or reinforced with the sheet 8 or a different sheet, the sheet or structure may break or deteriorate due to aging. The primer layer 6 can be formed by applying the above-mentioned coating composition to the broken or deteriorated position in the sheet. The structure can be repaired or reinforced again by pasting a new sheet 8 to the primer layer 6. By pasting a new sheet 8 to an old sheet, the value of the structure can be maintained and maintained for an extremely long period of time. The pasting can be achieved by the bonding adhesion of the primer layer 6. In the re-repair and re-reinforcement, the old sheet does not need to be discarded. In the re-repair and re-reinforcement, waste generation can be suppressed. The primer layer 6 conforms to the purpose of the circular economy. Since the new sheet 8 has a low density, even when the new sheet 8 is laminated on the old sheet, the adverse effect on the seismic resistance of the structure is small.
[0102] Examples Hereinafter, the effects of the sheet according to the examples will be explained. The scope of the present specification should not be construed as being limited based on the description of these examples.
[0103] [Experiment 1 Coating composition] [Example 1] 19.9 parts by mass of trimethylolpropane triglycidyl ether (trade name "DENACOL EX-321L" manufactured by Nagase ChemteX Corporation) as an epoxy compound, 53.9 parts by mass of 3-aminopropyltrimethoxysilane (Tokyo Chemical Industry Co., Ltd.) as an aminosilane compound, and 26.2 parts by mass of 3-glycidyloxypropyltrimethoxysilane (Tokyo Chemical Industry Co., Ltd.) as an alkoxysilane-containing epoxy compound were injected into a Pyrex glass separable flask. These compounds were mixed together at 60°C and a nitrogen stream at normal pressure for 2.5 hours, and reacted. 100 parts by mass of ethanol 100 were added thereto to terminate the reaction, thereby obtaining a partial reaction product having a gel fraction of 50%.
[0104] 100 parts by mass of a polymer containing an alkyl (meth)acrylate monomer unit in the main chain ("DIANAL BR105" manufactured by Mitsubishi Chemical Corporation, weight average molecular weight: 45000) was dissolved in 100 parts by mass of ethanol to obtain an acrylic resin solution. 25 parts by mass of the partial reaction product and 100 parts by mass of the acrylic resin solution (100 parts by mass in terms of solid content) were kneaded together with a ball mill to obtain a coating composition.
[0105] [Example 2] A coating composition was obtained in the same manner as in Example 1, except that 100 parts by mass of the acrylic resin solution and 10 parts by mass of the partial reaction product were kneaded together.
[0106] [Example 3] A coating composition was obtained in the same manner as in Example 1, except that 100 parts by mass of the acrylic resin solution and 90 parts by mass of the partial reaction product were kneaded together.
[0107] [Example 4] A coating composition was obtained in the same manner as in Example 1, except that the reaction time under nitrogen flow was set to 1.0 hour. A partial reaction product having a gel fraction of 35% was obtained from the reaction.
[0108] [Example 5] A coating composition was obtained in the same manner as in Example 1, except that the reaction time under nitrogen flow was set to 4.0 hours. A partial reaction product having a gel fraction of 60% was obtained from the reaction.
[0109] [Comparative Example 1] 100 parts by mass of a polymer containing an alkyl (meth)acrylate monomer unit (the above-mentioned "DIANALBR105") was dissolved in 100 parts by mass of ethanol to obtain a coating composition.
[0110] [Comparative Example 2] 66.7 parts by mass of an epoxy resin (trade name “E2300 main agent” manufactured by Konishi Co., Ltd.) and 33.3 parts by mass of a polyamidoamine-modified aliphatic polyamine (“E2300 curing agent” manufactured by Konishi Co., Ltd.) were mixed together to obtain a coating composition.
[0111] [Comparative Example 3] 19.9 parts by mass of trimethylolpropane triglycidyl ether (the above-mentioned trade name "DENACOL EX-321L" manufactured by Nagase Chemicals Co., Ltd.), 53.9 parts by mass of 3-aminopropyltrimethoxysilane (Tokyo Chemical Industry Co., Ltd.), and 26.2 parts by mass of 3-glycidyloxypropyltrimethoxysilane (Tokyo Chemical Industry Co., Ltd.) were injected into a container. These compounds were stirred at a temperature of 23°C for 30 minutes to obtain a mixture. The mixture had a gel fraction of 0%. 25 parts by mass of the mixture and 100 parts by mass of the acrylic resin solution used in Example 1 were kneaded together with a ball mill to obtain a coating composition.
[0112] [Test piece used for evaluation] Artificial slate (trade name "COLONIAL-GLASSA" manufactured by KMEW Co., Ltd.) was irradiated with a xenon lamp using a weather meter. The irradiation conditions were as follows: Weather meter: Super Xenon Weather Meter (“SX-75” manufactured by Suga Test Instruments Co., Ltd.) Black panel temperature: 63°C Humidity: 55% Irradiance: 180 W / m at 300 to 400 nm 2 Irradiation time: 5000 hr.
[0113] The coating composition was applied to the artificial slate. The amount applied was 200 g / m 2 The coating composition was dried at a temperature of 23° C. until the coating composition became dust-free and lost its tackiness, and a primer layer having a thickness of 80 μm was obtained.
[0114] [Manufacturing of Sheet Material] A coating material containing an acrylic silicone-based resin was applied to a release paper made of PP laminated paper and having a thickness of 130 μm. The coating material was an emulsion composition containing 60 parts by mass of an acrylic silicone resin, 25 parts by mass of titanium dioxide, 10 parts by mass of iron oxide, and 5 parts by mass of carbon black. The coating material was dried to obtain a functional layer having a thickness of 100 μm.
[0115] Different coating materials are applied to the functional layer. The coating material is a water-based acrylic emulsion containing 45 parts by mass of a cement mixture. The cement mixture contains 70 ± 5 parts by mass of portland cement, 10 ± 5 parts by mass of silicon dioxide, 2 ± 1 parts by mass of aluminum oxide and 1 to 2 parts by mass of titanium oxide. The acrylic emulsion contains 53 ± 2 parts by mass of an acrylic acid-based polymer and 43 ± 2 parts by mass of water, and the acrylic acid-based polymer is obtained by emulsion polymerization using an acrylate monomer as an emulsifier. The coating material is dried to obtain an intermediate layer (polymer-cement solidified layer). In the intermediate layer, portland cement has been dispersed in an acrylic resin. The content ratio of portland cement is 50% by mass.
[0116] A cheesecloth with a mesh count of 520 (trade name "V520" manufactured by UNITIKA Trading Co., Ltd., thickness: 220 µm, material: vinylon, basis weight: 32 g / m 2 ) is laminated onto this intermediate layer. The total thickness of the intermediate layer and the cheesecloth is 300 µm.
[0117] A mixed solution for an adhesive was prepared by mixing together 100 parts by mass of an acrylic adhesive (the product name "ORIBAIN 6574" described above) and 6 parts by mass of an isocyanate-based curing agent (the product name "BHS 8515" manufactured by Toyo Chemical Co., Ltd.). The mixed solution for an adhesive was applied to the surface of cheesecloth. The mixed solution was dried to form an adhesive layer having a thickness of 200 µm, thereby obtaining a sheet having a total thickness of 600 µm.
[0118] [Initial bonding adhesion] The sheet was pasted onto the primer layer with a pressure roller having a mass of 2 kg. A double-sided tape (trade name "No. 5015" manufactured by Nitto Denko Corporation) was pasted onto the surface of the functional layer of the sheet. A film having a thickness of 100 μm and made of PET was pasted onto the surface of the tape to obtain a laminate. After 24 hours, the laminate was subjected to a 180° peel test. The test conditions were as follows: Width of test piece: 25 mm Temperature: 23°C Humidity: 50% Tester: AUTOGRAPH ("AGX-V 10 kN" manufactured by Shimadzu Corporation) Peeling speed: 300 mm / min The results are shown in Tables 1 and 2 below.
[0119] [Long-term bonding adhesion] The test piece obtained by the same method as the test piece for evaluating the initial bonding adhesion was irradiated with a xenon lamp using a weather meter. The irradiation conditions were as follows: Weather meter: Super Xenon Weather Meter ("SX-75" manufactured by Suga Testing Instruments Co., Ltd.) Black panel temperature: 63°C Humidity: 55% Irradiance: 180 W / m at 300 to 400 nm 2 Irradiation time: 5000 hr The test piece was subjected to a 180° peel test. The test conditions were the same as those for the 180° peel test for initial bond adhesion. The results are shown in Tables 1 and 2 below.
[0120] [Sealing characteristics] The sheet was pasted onto the primer layer. After 30 minutes, the sheet was peeled off from the substrate. The peeling state was visually observed and rated according to the following criteria: A: Peeling occurs at the interface between the sheet and the primer layer (cohesive failure). B: Peeling occurs at the interface between the primer layer and the artificial slate (interface failure). The results are shown in Tables 1 and 2 below.
[0121] [Processability] The time taken for the coating composition to dry in the formation of the above primer layer was measured. These results are shown in Tables 1 and 2 below.
[0122] [Applicable period] The coating composition for the primer layer was kept at a temperature of 23°C for five hours. The occurrence of gelation was confirmed every hour. The time taken for gelation to occur is the pot life. These results are shown in Tables 1 and 2 below.
[0123] [Insect repellency] The artificial slate covered with the primer layer was kept outdoors for two hours, and the number of insects (bees, etc.) gathered on the primer layer was counted and rated according to the following criteria: A: The number of insects is nine or less, B: The number of insects is 10 or more, The results are shown in Tables 1 and 2 below.
[0124] [Table 1] .
[0125] [Table 2] .
[0126] As is apparent from Tables 1 and 2, the coating composition of each example is excellent in various properties. The advantages of these coating compositions are apparent from these evaluation results.
[0127] [Experiment 2: Encapsulation Structure] [Example 6] An aluminum-zinc alloy-plated steel sheet (a flat GALVALUME steel sheet manufactured by Q-ho Metal Works) was prepared. The plated layer in the steel sheet contained 55.0 mass % Al, 43.4 mass % Zn, and 6.0 mass % Si. For the steel sheet, the contact angle θ1 was 77.5°, the contact angle θ2 was 45.4°, and the γ SV d is 33.1 mJ / m 2 , γ SV h is 6.0 mJ / m 2 , and the surface free energy γ is 39.1 mJ / m 2The coating composition of Example 1 was applied to the steel plate (adherent). The application amount was 400 g / m 2 The coating composition was kept at a temperature of 100°C for five minutes and dried to obtain a primer layer. Figures 1 to 3 The sheet shown. The sheet has an adhesive layer. The adhesive layer is obtained from an adhesive composition (the above-mentioned "ORIBAIN BPS5565K"). For the adhesive layer, the contact angle θ1 is 108.6°, the contact angle θ2 is 60.5°, and the γ SV d is 29.5 mJ / m 2 , γ SV h is 0 mJ / m 2 , and the surface free energy γ is 29.5 mJ / m 2 .
[0128] [Examples 7 and 8 and Comparative Examples 4 to 6] The coated construction was obtained in the same manner as in Example 6, except that the composition of the primer layer was changed as shown in the following Tables 3 and 4. The details of the composition are as follows: Comparative Example 4: Coating composition containing acrylic silicone resin as a base material (product name "Belle Earth Elastic Black" manufactured by Fujikura Chemicals, Ltd.) Comparative Example 5: A mixture of a coating composition containing an acrylic silicone resin as a base material (the above-mentioned "BelleEarth Elastic Black") and another coating composition containing an acrylic silicone resin as a base material (product name "CL-CB1 BLACK (P5)" manufactured by Dainichi Seika Industries, Ltd.) (mass mixing ratio: 50 / 50) Example 7: Mixture of a water-based aluminum hydroxide dispersion (product name "9216AO" manufactured by Tokushiki Co., Ltd.) and an ethylene-vinyl acetate copolymer (product name "SUMIKAFLEX S-400HQ" manufactured by Sumika Chemtex Co., Ltd.) (mass mixing ratio: 50 / 50) Example 8: A mixture of a water-based aluminum hydroxide dispersion (the above-mentioned "9216AO") and the coating composition of Example 1 (mass mixing ratio: 50 / 50) Comparative Example 6: A coating composition containing a silicone resin as a base material (product name “SK PREMIUM SILICONE” manufactured by SKKAKEN Co., Ltd.).
[0129] [Peel test] The coated construction was subjected to peel testing. The peeling location was visually observed and the peeling interface was determined. These results are shown in Tables 3 and 4 below.
[0130] [Table 3] .
[0131] [Table 4] .
[0132] As is apparent from Tables 3 and 4, in the coating construction of each example, peeling occurred at the interface between the primer layer and the adhesive layer. The advantages of these coating constructions are apparent from these evaluation results.
[0133] [Disclosed items] Each of the following items discloses a preferred embodiment.
[0134] [Project 1] A coating composition comprising (1) a polymer comprising an alkyl (meth)acrylate monomer unit in its main chain, and (2) A partial reaction product of a mixture containing an epoxy compound and an aminosilane compound.
[0135] [Project 2] The coating composition according to item 1, wherein, in the partial reaction product (2), gelation due to the reaction between the epoxy compound and the aminosilane compound does not occur.
[0136] [Item 3] The coating composition according to item 1 or 2, wherein the amount of the partial reaction product (2) is 1 part by mass or more and 150 parts by mass or less relative to 100 parts by mass of the polymer (1).
[0137] [Item 4] The coating composition according to any one of items 1 to 3, wherein the ratio (Y / X) of the number of amino groups and / or imino groups (Y) in the aminosilane compound to the number of epoxy groups (X) in the epoxy compound in the mixture is 0.2 or more and 1.5 or less.
[0138] [Item 5] The coating composition according to any one of items 1 to 4, wherein the mixture further contains an alkoxysilane-containing epoxy compound.
[0139] [Item 6] The coating composition according to item 5, wherein the ratio of the amount of the alkoxysilane-containing epoxy compound to the total amount of the epoxy compound, the aminosilane compound and the alkoxysilane-containing epoxy compound in the mixture is 10% by mass or more and 40% by mass or less.
[0140] [Item 7] A method for producing a coating composition, the method comprising: A: preparing a mixture containing an epoxy compound and an aminosilane compound, B: a step of reacting the mixture, C: a step of terminating the reaction of the mixture before the reaction between the epoxy compound and the aminosilane compound causes gelation to obtain a partial reaction product, and D: A step of mixing a polymer comprising an alkyl (meth)acrylate monomer unit in the main chain with the partial reaction product.
[0141] [Item 8] A method for protecting a structure, the method comprising: A: applying a coating composition to a surface of the structure to obtain a primer layer, the coating composition comprising a polymer containing a (meth) alkyl acrylate monomer unit in the main chain and a partial reaction product of a mixture containing an epoxy compound and an aminosilane compound, and B: A step of attaching a sheet having a functional layer and an adhesive layer to the primer layer by the adhesive force of the adhesive layer.
[0142] [Item 9] The protection method according to item 8, wherein, in the step B, a sheet in which the material of the adhesive layer is an adhesive composition and the base material of the composition is an acrylic resin is pasted onto the primer layer.
[0143] [Item 10] The protection method according to item 8 or 9, wherein, in the step B, a sheet in which an intermediate layer is provided between the functional layer and the adhesive layer and the intermediate layer contains a polymer and cement dispersed in a matrix of the polymer is pasted onto the primer layer.
[0144] [Item 11] A structure covering structure, comprising a primer layer located on the structure, an adhesive layer located on the primer layer, and a functional layer located on the adhesive layer. wherein an adhesion workload W2 between the primer layer and the adhesive layer is smaller than an adhesion workload W1 between the structure and the primer layer, and a ratio (W1 / W2) of the adhesion workload W1 to the adhesion workload W2 is 1.20 or greater.
[0145] [Item 12] The coating structure according to item 11, wherein the 180° peel force between the primer layer and the adhesive layer measured in accordance with the provisions in JIS Z 0237 (2022) is 1.51 N / 25 mm or higher.
[0146] Industrial Applicability The coating compositions thus described can be used as primers for a variety of constructions.
[0147] List of Reference Numerals 2. Roof 4. Encapsulation structure 6. Primer layer 8···Sheet 10···Functional layer 12···Middle Layer 14···Adhesive layer 16···Reinforcement 18···Yarn 18a···Meridian 18b···Weft 20···grid.
Claims
1. A structure covering structure, comprising: A primer layer located on the structure; an adhesive layer disposed on the primer layer; and a functional layer located on the adhesive layer, wherein an adhesion workload W2 between the primer layer and the adhesive layer is smaller than an adhesion workload W1 between the structure and the primer layer, and a ratio (W1 / W2) of the adhesion workload W1 to the adhesion workload W2 is 1.20 or greater.
2. The covering structure according to claim 1, wherein: The 180° peel force between the primer layer and the adhesive layer measured in accordance with the provisions in JIS Z 0237 (2022) is 1.51 N / 25 mm or higher.
3. A coating composition comprising: (1) A polymer comprising alkyl (meth)acrylate monomer units in its main chain; and (2) A partial reaction product of a mixture containing an epoxy compound and an aminosilane compound.
4. The coating composition according to claim 3, wherein In the partial reaction product (2), gelation due to the reaction between the epoxy compound and the aminosilane compound does not occur.
5. The coating composition according to claim 3 or 4, wherein The amount of the partial reaction product (2) is 1 part by mass or more and 150 parts by mass or less relative to 100 parts by mass of the polymer (1).
6. The coating composition according to claim 3 or 4, wherein A ratio (Y / X) of the number of amino groups and / or imino groups (Y) in the aminosilane compound to the number of epoxy groups (X) in the epoxy compound in the mixture is 0.2 or more and 1.5 or less.
7. The coating composition according to claim 3 or 4, wherein The mixture further contains an alkoxysilane-containing epoxy compound.
8. The coating composition according to claim 7, wherein A ratio of the amount of the alkoxysilane-containing epoxy compound to the total amount of the epoxy compound, the aminosilane compound, and the alkoxysilane-containing epoxy compound in the mixture is 10% by mass or more and 40% by mass or less.
9. A method for producing a coating composition, the method comprising: A: a step of preparing a mixture containing an epoxy compound and an aminosilane compound; B: a step of reacting the mixture; C: a step of terminating the reaction of the mixture before the reaction between the epoxy compound and the aminosilane compound causes gelation to obtain a partial reaction product; and D: A step of mixing a polymer comprising an alkyl (meth)acrylate monomer unit in the main chain with the partial reaction product.
10. A method for protecting a structure, the method comprising: A: a step of applying a coating composition containing a polymer including an alkyl (meth)acrylate monomer unit in a main chain and a partial reaction product of a mixture containing an epoxy compound and an aminosilane compound to a surface of a structure to obtain a primer layer; and B: A step of attaching a sheet having a functional layer and an adhesive layer to the primer layer by the adhesive force of the adhesive layer.
11. The protection method according to claim 10, wherein: In the step B, a sheet in which the material of the adhesive layer is an adhesive composition and the base material of the composition is an acrylic resin is attached to the primer layer.
12. The protection method according to claim 10 or 11, wherein: In the step B, a sheet in which an intermediate layer is provided between the functional layer and the adhesive layer and contains a polymer and cement dispersed in a matrix of the polymer is pasted onto the primer layer.
Citation Information
Patent Citations
Curable composition
JP2003313397A
Method for repairing roof
JP2022101896A